El Género Glandularia (Verbenaceae) En Argentina - Peralta, Paola Fernanda (2011)
A taxonomic study of the species of the genus Glandularia J. F. Gmel. is presented for Argentina, with 33 species and four varieties, of which 12 taxa are exclusive to the region of study, representing the area of greatest diversity in southern South America. These taxa are distributed from the province of Jujuy in the north to the province of Santa Cruz in the south. The inclusive species are delimited in this study and nomenclatural problems and typifications are clarified. The following plant names are neotypified: Verbena platensis Spreng. Lectotypifications are provided for V. aristigera S. Moore, V. aurantiaca Speg., V. calliantha Briq., V. chamaedryfolia Juss. f. foliosa Chodat, V. flava Gillies & Hook. ex Hook., V. hassleriana Briq., V. incisa Hook., V. megapotamica Spreng., V. melindres Gillies, V. melindroides Cham., V. mendocina Phil., V. phlogiflora Cham., V. phlogiflora var. mucilenta Schauer, V. sanguinea Larrañaga, V. scordioides Cham., V. selloi Spreng., V. stellarioides Cham., V. stellarioides var. sessilis Cham., V. sulphurea D. Don var. pedunculata Gay, V. tenera Spreng., V. teucrioides Gillies & Hook. ex Hook., V. tweedieana Niven ex Hook. var. arraniana Niven in Maund & Hensl. ex Maund. One new combination at subspecific level is made: G. aurantiaca (Speg.) Botta var. glabra (Hicken) P. Peralta, and three at specific level: G. andalgalensis (Moldenke) P. Peralta, G. andina (Griseb.) P. Peralta, and G. tweedieana (Niven ex Hook.) P. Peralta. Included is a key to identify the species and varieties in Argentine Glandularia, which are described and illustrated.